2005
DOI: 10.1210/jc.2005-0550
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational Effects of Posttraumatic Stress Disorder in Babies of Mothers Exposed to the World Trade Center Attacks during Pregnancy

Abstract: The data suggest that effects of maternal PTSD related to cortisol can be observed very early in the life of the offspring and underscore the relevance of in utero contributors to putative biological risk for PTSD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

20
379
0
9

Year Published

2006
2006
2015
2015

Publication Types

Select...
4
4

Relationship

3
5

Authors

Journals

citations
Cited by 638 publications
(408 citation statements)
references
References 20 publications
20
379
0
9
Order By: Relevance
“…We have previously suggested that parental PTSD may confer risk of PTSD in the offspring by affecting the predisposition to a modification that may later affect the response to a traumatic event (Yehuda et al, 2005;Yehuda et al, 2007a). This hypothesis is raised by the demonstration that low plasma cortisol levels in offspring are also associated particularly with maternal PTSD (Yehuda et al, 2007b).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously suggested that parental PTSD may confer risk of PTSD in the offspring by affecting the predisposition to a modification that may later affect the response to a traumatic event (Yehuda et al, 2005;Yehuda et al, 2007a). This hypothesis is raised by the demonstration that low plasma cortisol levels in offspring are also associated particularly with maternal PTSD (Yehuda et al, 2007b).…”
Section: Discussionmentioning
confidence: 99%
“…The possibility that low cortisol in offspring was a transmitted risk factor was further supported by observations of lower salivary cortisol levels in year old infants born to mothers with PTSD compared to infants born to mothers without PTSD, following their direct exposure to the collapse of the World Trade Center on 9/11 during pregnancy (Yehuda et al, 2005). Although the contribution of paternal PTSD to cortisol levels in infant offspring was not examined, there was a significant effect of trimester (i.e., the effect was most present in the third trimester), consistent with in utero contributions to low cortisol in offspring.…”
Section: Introductionmentioning
confidence: 97%
“…Observations from the Dutch Famine study and others have demonstrated that parental stress may be transmitted via the gametes (Franklin et al, 2010;Dias and Ressler, 2014;Gapp et al, 2014) or the gestational uterine environment (Yehuda et al, 2005). More recently, animal work has demonstrated that variations in early maternal care (originally induced by the stress of removing mothers from pups and briefly handling the mothers before returning them to the home cage) results in altered neural, hormonal, cognitive, and behavioral responses in pups, that were not directly manipulated except for the brief separation from the mother, and the mother's behavior upon return (Liu et al, 1997;Caldji et al, 1998;Weaver et al, 2004).…”
Section: What Is the Intergenerational Transmission Of Stress?mentioning
confidence: 99%
“…This was true, even though in all cases offspring were born after World War II. It has also been shown that women who develop PTSD as a result of trauma exposure during pregnancy-such as having to evacuate the World Trade Center on 9/11-give birth to affected offspring with evidence of a trimester effect (Yehuda et al, 2005). The greater influence of maternal exposure during the third compared with second trimester provides evidence for the relevance of in utero effects to the transmission of biological risk.…”
Section: Clinical Observations and Significancementioning
confidence: 99%
“…Similarly, individuals conceived during the Dutch Hunger Winter during the Second World War showed hypomethylation at the insulinlike growth factor 2 gene (IGF2) and were more prone to obesity when tested decades later [9]. Another recently reported example is the transgenerational effects of posttraumatic stress disorder in babies of mothers exposed to the 9/11 terrorist attacks during pregnancy [10,11].…”
mentioning
confidence: 99%